2021
DOI: 10.1080/26395940.2021.1982406
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of low-molecular-weight organic acids on remobilization of Cd, Cr, Pb, and As in alkaline coastal wetland soil

Abstract: Low-molecular-weight organic acids (LMWOAs) that have a wide variety of biological activities can affect the mobilization of heavy metals in soil. In this study, the effects of three kinds of LMWOAs on the remobilization of Cd, Cr, Pb, and As were investigated. The results showed that the concentrations of Cr, Pb, and As reached the maximum values at 7 d, and then decreased at 58 d, indicating that the LMWOAs induced the release of these elements from soil. The ability of LMWOAs to affect the mobility of Cr an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The increased effect of citric acid on the metal leaching could be explained by the fact that it contains three carboxyl groups, while oxalic acid has two carboxyl groups. Citric acid can therefore form tridentate ligands (six-membered ring structures) with metals; larger complex compounds that are usually more stable and more mobile than the smaller bidentate metal-oxalate ligands [ 38 , 73 ]. The stability of organic acid complexes with metals is indicated by their respective stability constants, being mostly higher for citrate complexes than for oxalate complexes [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased effect of citric acid on the metal leaching could be explained by the fact that it contains three carboxyl groups, while oxalic acid has two carboxyl groups. Citric acid can therefore form tridentate ligands (six-membered ring structures) with metals; larger complex compounds that are usually more stable and more mobile than the smaller bidentate metal-oxalate ligands [ 38 , 73 ]. The stability of organic acid complexes with metals is indicated by their respective stability constants, being mostly higher for citrate complexes than for oxalate complexes [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aqueous solutions of citric and oxalic acids at two concentration levels (0.1 and 1.0 mM) were used to simulate the static leaching of metal (loid)s and anions from six MSWI ash samples with high total concentrations of metal (loid)s (S7, S8, S9a, b and S10a, b) under rhizosphere conditions. The reason was that the plant cover and soil microorganisms represent a continuous source of many organic acids, which significantly affect the adsorption and leaching behaviour of chemical elements in soils and other solid materials [ [37] , [38] , [39] , [40] , [41] ]. The initial pH values were 5.45 and 3.50 for 0.1 and 1.0 mM citric acid solutions, and 4.90 and 3.20 for 0.1 and 1.0 mM oxalic acid solutions, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Humic substances have a higher affinity for Pb 2+ and Cu 2+ , and the higher the pH of the solution, the higher their adsorption [ 26 , 59 ]. Malic acid (MA) can form soluble complexes with heavy metals, facilitating their migration into the liquid phase [ 2 , 60 ], with properties of high biodegradability, low toxicity, low price, and being environmentally friendly [ 1 , 61 , 62 , 63 , 64 ]. Studies have shown that by using malic acid, heavy metals are extracted from polluted soils with an efficiency of 50.8%, according to literature reports [ 65 ], or even 63.39–88.65%, as reported by Zhao [ 1 ], for the case of Pb.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies of the effects of phosphate on As behavior with the participation of microorganisms in soils. More consideration has been given to the physicochemical effects of LMWOAs on As migration in soils [33][34][35][36][37][38]. However, there has been comparatively little consideration of the role of microorganisms in the action of LMWOAs [39,40].…”
Section: Introductionmentioning
confidence: 99%